WATER QUALITY OF THE LAGUNA DE TRAGADERO WETLAND IN THE PROVINCE OF JAUJA – JUNIN - Misari-Chuquipoma, Emilia (2024)
The objective of the research is to determine the water quality of the Laguna de Tragadero Wetland contaminated by domestic sewage disposal using the ICA-NSF methodology established by the National Sanitation Foundation of the United States (NSF). For this purpose, physico-chemical and microbiological parameters such as dissolved oxygen, biochemical oxygen demand, total dissolved solids, turbidity, pH, temperature, nitrates, phosphates and faecal coliforms were determined. The samples were collected during the summer and flood period to then process the data and determine the water quality of the water body under study. It was concluded that the water condition is in the range of 43.35 to 48.61 with an average value of 45.98 which indicates that it is not appropriate for aquatic life, according to the categorization of the ICA-NSF proposed by Brown corresponds to poor quality. The body of water is being affected by the discharge of remaining water from the Domestic Wastewater Treatment Plant of the district of Acolla, as well as the use of agricultural fertilizers in farming areas near the wetland and the activity of livestock grazing is affecting the conservation of the aquatic environment.